THE CALCULATION OF THE EFFICIENCY OF INFORMATION PROTECTION FROM UNAUTHORIZED ACCESS TO RESOURCES OF INFORMATION SYSTEM - Igor Vladimirovich Kaliberda; Anton Igorevich Belobragin (Современная наука и инновации)
Considers the problem of analysis of physical protection information to the object information. To solve the problem is proposed the method of calculation of efficiency of physical protection systems using simulation method. Simulation and evaluation are conducted using software modules KALIGOR and EASI. The analysis of options with recommendations for improving the system of protection.